Isolasi dan Karakterisasi Mikroorganisme Pendegradasi Hidrokarbon dari Tanah Tercemar Minyak Bumi - Isna Ayu Nur Febriana (Fakultas Teknik, 2025)
Oil pollution in soil is an environmental issue that needs to be addressed because these pollutants are toxic and difficult to break down naturally. This study aims to analyse the characteristics of hydrocarbon-degrading bacterial isolates obtained from oil-contaminated soil and to analyse the effect of varying concentrations of solar and incubation time on the growth of bacterial isolates from hydrocarbon-contaminated soil. The method used was serial dilution bacterial isolation on MSM (Mineral Salt Medium) with the addition of varying concentrations of diesel fuel at 2%, 5%, and 10%, followed by observation of growth through direct counting of colonies in CFU/ml units at incubation times ranging from 24 hours to 144 hours. The results showed that a 2% solar concentration yielded the highest growth between 48 and 72 hours, while a 10% concentration exhibited the lowest growth. In conclusion, solar concentration influences bacterial growth rates, with lower concentrations tending to be more optimal for the tested isolates.
Reupload File Repository 4 Juni 2026_Yudi :: Finalisasi Repositori File 7 Juni 2026_Kurnadi
Keywords: Screening; Characterisation; Oil-Contaminated; Hydrocarbons